THE INFLUENCE OF HALAL SOCIALIZATION AND BUSINESS CAPITAL ON INTEREST OF HALAL CERTIFICATION IN SURABAYA MSMES - Cantik Siska Anggraeni; Moch. Khoirul Anwar (Universitas Islam Negeri Mataram, 2023)
MSMEs in East Java have not fully obtained halal certification. Even though regulations regarding the obligation to obtain halal certification for MSMEs have been stipulated. UMKM Surabaya itself still has not reached 50% who pocketed halal certification. MSMEs do not fully understand the regulations and procedures for administering halal certification. Therefore, the government should try to provide facilities that make it easy for MSMEs to take care of halal certification. This study intends to determine the effect of halal socialization and business capital on the Interest in halal certification for UMKM in Surabaya City. The independent variable of this study consisted of two variables, namely halal socialization and venture capital, while the dependent variable of this study, namely the Interest in halal certification for UMKM in Surabaya City. This study was compiled using a quantitative method through a sample of 100 respondents. The questionnaires were distributed using a Likert scale on halal socialization and business capital. This study showed that the variables of halal socialization and business capital affected the Interest in halal certification for UMKM in Surabaya City. As for the test results of the coefficient of determination (R Square), it was found that the variables of halal socialization and business capital have a simultaneous effect of 71.4% on the Interest in halal certification for UMKM in Surabaya City.